Different protocols - different situations - different genotypes from the research laboratory to application in genebanks Some subjects of discussion - Keller, E. R. Joachim; Senula, A; Büchner, D; Kaczmarczyk, A; Zanke, C (MTT, 2008)
Genebanks are application fields of preservation and maintenance methods, also of those for cryopreservation, in a broader scale. When moving some scientific method from the state of fundamental research in a university s laboratory into broader application, some aspects have to be considered. The main problems are: 1. In/stability of a given method. We need to be sure that the method developed under experimental conditions using a model genotype is applicable also under every-days laboratory conditions which may differ with the season, with the personnel, sometimes with fluctuations in surrounding technical parameters. They should be applicable with other genotypes than the models as well and they should be not too sensitive in circumstances when material is not grown or received under optimum conditions. Some factors which influence the results are the physiological conditions of the material and hidden endophytes. 2. Logistics using a method in a larger scale. Whereas the attention of a fundamental researcher can be drawn on every single step of the procedure, and it is no need to limit his time for one given part of the protocol, in routine work it is necessary to pass all the steps sufficiently quick to get an efficient amount of explants into cryopreservation. Therefore, the simplest and shortest protocol will always have priority when decision between several options is needed. Furthermore, the output of the whole procedure is depending on the number of acting persons. Should we have more persons available, specialisation could take place. This is especially important in regard of the explant preparation procedures. Participation of several persons will, on the other hand, increase the standardisation needs. 3. Genbanks are the most capable actors to compare aspects of cryopreservation in a range of taxa within a given systematic group. This potential is by far not fully utilised. It would be interesting to compare species in a given group which differ in certain parameters e. g. water content (e. g. there are genera where there is a full range from water plants to succulents, or use of resurrection plants), cold- or salt tolerance. Results obtained in routine screening in genebanks could, thus, give another feed-back link to fundamental research. 4. Finally, the existence of a well-elaborated method is only one prerequisite for success in genebanks. Collaboration between several laboratories will increase the general effect of these methods by mutual validation and chances to establish safety duplication systems.
Keywords: Ka; stability of a method; standardisation; safety duplication systems